Fairy tail. 37 - Mashima, Hiro, 1977- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2014)
"To the surprise of no one, Natsu hasn't really thought through his plan to rescue Lucy. Along the way, they face a death trap, a team of magical executioners, and...another Lucy?! Meanwhile Erza struggles through a three-way free-for-all with the world's other two most powerful women wizards! Will the world survive Fairy Tail's attempts to save it?!" -- Back cover.